Zebrafish as a Model for Obesity and Diabetes - Zang, Liqing; Maddison, Lisette A.; Chen, Wenbiao (Frontiers in Cell and Developmental Biology, 2018)
Obesity and diabetes are epidemics rising worldwide. The prevalence rates of diabetes are increasing in parallel with the rates of obesity and the strong connection between these two diseases and has been coined as “diabesity”. The health risks of overweight or obesity include Type 2 diabetes mellitus (T2DM), coronary heart disease and cancer of numerous organs. Both obesity and diabetes are complex diseases that involve the interaction of genetics and environmental factors. The underlying pathogenesis of obesity and diabetes are not well understood and further research is needed for pharmacological and surgical management. Consequently, the use of animal models of obesity and/or diabetes is important for both improving the understanding of these diseases and identify and develop effective treatments. Zebrafish is an attractive model system for studying metabolic diseases because of the functional conservation in lipid metabolism, adipose biology, pancreas structure, and glucose homeostasis. It is also suited for identification of novel targets associated with the risk and treatment of obesity and diabetes in humans. In this review, we highlight studies using zebrafish to model metabolic diseases, and discuss the advantages and disadvantages of studying pathologies associated with obesity and diabetes in zebrafish.